Study of Biodiesel Production from Sunflower Oil Using Non Usual Basic Polymeric Resin as Catalyst - da Silva, Viviane Fernandes; Santa Maria, Luiz Claudio de; Goncalves, Lenise V.F.; Fonseca, Mauricio G.; Batista, Luciano N. (Journal of Technology Innovations in Renewable Energy, 2013)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Biodiesel is defined as a long-chain mono alkyl (methyl, ethyl or propyl) ester of fatty acids obtained from renewable sources by transesterification reaction using an acid or base. In this work, a basic resin, Amberlyst A26, was used to produce methyl sunflower biodiesel. The iodine value, corrosion to copper, oxidative stability, specific mass, water content, acid value, cloud point and ester composition were evaluated. The heterogeneous catalyst was also characterized to verify its efficiency and its ability to be reused. We used the following analytical techniques: scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-rays fluorescence (XRF) and differential scanning calorimetry (DSC). The results showed that the characteristics of biodiesel made from sunflower oil using resin A26 as a catalyst are in accordance with Brazilian biodiesel regulations, except the oxidative stability. The techniques used to characterize the resin showed that it is possible to reuse the resin after regeneration. <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->